2015
DOI: 10.4028/www.scientific.net/amm.787.523
|View full text |Cite
|
Sign up to set email alerts
|

Abrasive Assisted Electrochemical Machining of Al-B<sub>4</sub>C Nanocomposite

Abstract: Aluminium reinforced with SiC, Al2O3 and B4C etc. possesses an attractive combination of properties such as high wear resistance, high strength to weight ratio and high specific stiffness. Among the various reinforced materials used for aluminium, B4C has outperformed all others in terms of hardening effect. Particle size reduction of B4C is found to have positive impact on the material hardness. In the view of physical properties, B4C has less density than that of SiC and Al2O3, which makes it an attractive r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The electrolyte is usually a mixture of NaNO3 or NaCl salt dissolved in water. It is extensively utilized for machining of cutting tools, medical components, automotive and aerospace components due to its advantages, such as the absence of thermal damage, good surface finish, high metal removal rate, and long wheel life [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrolyte is usually a mixture of NaNO3 or NaCl salt dissolved in water. It is extensively utilized for machining of cutting tools, medical components, automotive and aerospace components due to its advantages, such as the absence of thermal damage, good surface finish, high metal removal rate, and long wheel life [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Metal reinforced ceramic materials such as Al-Al2O3, Al-SiC, Al-B4C, and WC-Co groups are not suitable to machine by the electrochemical (ECM) and electrochemical grinding (ECG) machining process for two reasons. The first is that materials are non-conductive while the second is that they are very hard [2][3][4][5][6][7] Recently, more interests have been focused on increasing the material removal rate, and improving the machining accuracy. K. Rajkumar, et al have studied the effect of using SiC of 50 µm particle size as abrasive in the abrasive assisted electrochemical machining process, and showed that abrasive assisted electrolyte aids in removing the precipitates, which gets formed during the electrochemical machining specially at high voltages.…”
Section: Introductionmentioning
confidence: 99%